Faktor yang Berhubungan dengan Ketepatan Kode Diagnosis Infeksi Saluran Kemih pada Dokumen Rekam Medis Rawat Inap di Rumah Sakit Umum Daerah Pakuhaji - Putri, Indah Annisa Hendra; Rois, Amika; Fransisca, Elza (Universitas Malahayati, 2023)
ABSTRACT The cause of urinary tract infections is still a concern for the health world because it can be a benchmark for the success of nursing care and can improve the quality of hospital services to be more effective and efficient. To achieve effective and efficient services, it is necessary to support the existence of a hospital unit that has a special task, namely the medical record unit. Medical records are said to be of high quality if they are precise, accurate, and timely. Some hospitals in Indonesia around (65%) have not been precise in determining the diagnosis code based on ICD-10. Inaccuracy in giving a diagnosis code that is still high can lead to wrong decisions in medical procedures. To find out the relationship between the accuracy of the urinary tract infection (UTI) diagnosis code in the inpatient medical record documents at the Pakuhaji Regional General Hospital based on graduate education, years of service and training. This research is quantitative descriptive. The population and sample in this study were 80 Medical Record Documents. From the results of the study, the accuracy of the code for the diagnosis of urinary tract infection was 76 (95%), and the code was incorrect as much as 4 (5%). The results of the statistical test using the chi square test, the accuracy of the diagnosis code with education graduates has a constant value because the medical record officer determines the diagnosis code for the D3 RMIK graduates. The results of chi square show that there is no significant related between the accuracy of the diagnosis code with years of service and training. It can be concluded that the inpatient medical record documents observed had the accuracy of the Urinary Tract Infection diagnosis code as much as 76 (95%) and 4 (5%) were incorrect. Suggestions for hospitals should be a coding audit team and coders who have never attended seminars and training on coding principles and whose working period ≤ 5 years must attend seminars and training. Keywords: Urinary Tract Infections, Medical Records, Education Graduates, Years of Service, Training ABSTRAK Penyebab terjadinya Infeksi Saluran Kemih masih menjadi perhatian bagi dunia kesehatan karena dapat menjadi patokan keberhasilan asuhan keperawatan dan dapat meningkatkan mutu pelayanan rumah sakit agar lebih efektif dan efisien. Untuk tercapainya pelayanan yang efektif dan efisien perlu didukung adanya unit rumah sakit yang memiliki tugas khusus yaitu unit rekam medis. Rekam medis dikatakan bermutu apabila rekam medis tepat dan akurat. Sebagian Rumah Sakit di Indonesia sekitar (65%) pada tahun 2020 belum tepat dalam penetapan kode diagnosis berdasarkan ICD-10. Ketidaktepatan dalam pemberian kode diagnosis yang masih tinggi dapat menyebabkan salah dalam pengambilan keputusan prosedur medis. Untuk mengetahui hubungan ketepatan kode diagnosis infeksi saluran kemih (ISK) pada dokumen rekam medis rawat inap di RSUD Pakuhaji berdasarkan pendidikan lulusan, masa kerja dan pelatihan. Penelitian ini dilakukan di RSUD Pakuhaji dan merupakan penelitian deskriptif kuantitatif. Populasi dan sampel pada penelitian ini 80 Dokumen Rekam Medis. Dari hasil penelitian ketepatan kode diagnosis infeksi saluran kemih sebanyak 76 (95%), dan tidak tepat sebanyak 4 (5%). Hasil uji statistik menggunakan uji chi square ketepatan kode diagnosis dengan lulusan pendidikan bernilai konstan karena petugas rekam medis yang melakukan penetapan kode diagnosis lulusan D3 RMIK. Hasil chi square menunjukan tidak ada hubungan yang signifikan antara ketepatan kode diagnosis dengan masa kerja dan pelatihan. Dapat disimpulkan bahwa dokumen rekam medis rawat inap yang diamati memiliki ketepatan kode diagnosis Infeksi Saluran Kemih sebanyak 76 (95%) dan 4 (5%) salah. Saran untuk rumah sakit sebaiknya tim audit koding dan kodinger yang belum pernah mengikuti seminar dan pelatihan prinsip koding dan masa kerjanya ≤ 5 tahun harus mengikuti seminar dan pelatihan. Kata Kunci: Infeksi Saluran Kemih, Rekam Medis, Lulusan Pendidikan, Masa Kerja, Pelatihan.